Analisis Praktik Sistem Informasi Akuntansi Lembaga Keuangan Mikro Syariah Melalui Penerapan Mobile Banking - Vicky Yuwandy (LP2M Sekolah Tinggi Ilmu Syariah Darul Falah Mataram, 2018)
Poverty is a huge danger to humanity and not a few people who fall into civilization are only due to poverty. Poverty reduction efforts continue to be promoted one of them by empowering groups with the development of Microfinance. A country with a Muslim majority like Indonesia, initiatives have been taken to implement Islamic microfinance institutions. One way to measure the financial performance of Islamic microfinance institutions is to look at the implementation of the Accounting Information System (AIS) in loan disbursement and loan repayment. To achieve maximum service performance, innovations such as the use of mobile banking are needed. Based on the above reasons, this study aims to determine the use of information technology in improving the quality of financial reporting on Micro Small and medium enterprises (MSMEs), and the practice of using e-services in facilitating accounting information systems for MSMEs using the services of Islamic Micro Finance in Bogor. This study uses quantitative methods. Data collection techniques using questionnaires, while data analysis techniques using multiple linear regression analysis with the help of SPSS 16. The results of the analysis show that the Accounting Information System has a significant effect on MSME actors facilitated by LKMS in Bogor Regency for financial reporting. On the results of simultaneous testing or F test shows the variable mobile banking has a significant positive effect on the accounting information system and research shows that most respondents use information technology to support their productivity.